Dietary iron intervention using a staple food product for improvement of iron status in female runners - Alaunyte, I.; Stojceska, V.; Plunkett, A.; Derbyshire, E. (Journal of the International Society of Sports Nutrition, 2014)
Background: Adequate nutrient intake is critically important for achieving optimal sports performance. Like all athletes, female runners require a nutritionally balanced diet to maintain daily activities and a successful training regime. This study investigates the effects of cereal product based dietary iron intervention on iron status of recreational female runners (n = 11; 32 ± 7yr; 239 ± 153 minutes exercise/week, of which 161 ± 150 minutes running activity/week; VO2max 38 ± 4 ml/kg/min).